Electrochemical Characterization of a Complex FeFe Hydrogenase, the Electron-Bifurcating Hnd From Desulfovibrio fructosovorans - Jacq-Bailly, Aurore; Benvenuti, Martino; Payne, Natalie; Kpebe, Arlette; Felbek, Christina; Fourmond, Vincent; Léger, Christophe; Brugna, Myriam; Baffert, Carole (Frontiers in Chemistry, 2021)
Hnd, a FeFe hydrogenase from Desulfovibrio fructosovorans, is a tetrameric enzyme that can perform flavin-based electron-bifurcation. It couples the oxidation of H2 to both the exergonic reduction of NAD+ and the endergonic reduction of a ferredoxin. We previously showed that Hnd retains activity even when purified under air unlike other electron-bifurcating hydrogenases. In this study, we describe the purification of the enzyme under O2-free atmosphere and its biochemical and electrochemical characterization. Indeed, despite its complexity due to its multimeric composition, Hnd can catalytically and directly exchange electrons with an electrode. We characterized the catalytic and inhibition properties of this electron-bifurcating hydrogenase using protein film electrochemistry of Hnd purified either under air (aerobic) or under O2-free (anaerobic) conditions and compared the electrochemical properties of aerobic- and anaerobic-purified Hnd. Hydrogenases are usually inactivated under oxidizing conditions in the absence of dioxygen and can then be reactivated, to some extent, under reducing conditions. We demonstrate that the kinetics of this high potential inactivation/reactivation for Hnd show original properties: it depends on the enzyme purification conditions and varies with time, suggesting the coexistence and the interconversion of two forms of the enzyme. We also compare Hnd properties (Km for H2, diffusion and reaction at the active site of CO and O2) with those of standard monomeric FeFe hydrogenases (those which cannot catalyze electron bifurcation) and show that Hnd catalytic properties are comparable to those of standard hydrogenases. These results suggest that the presence of the additional subunits, needed for electron bifurcation, changes neither the catalytic behavior at the active site, nor the gas diffusion kinetics but induces unusual rates of high potential inactivation/reactivation.